Hubungan Penambahan Berat Badan Ibu Selama Kehamilan Dengan Berat Badan Bayi Lahir (Studi Di Polindes Desa Wonoayu Kecamatan Pilangkenceng Kabupaten Madiun Tahun 2013) - Sari, Dyah Permata (MEDICA MAJAPAHIT, 2015)
Weight gain during pregnancy in Indonesia are generally low (<10 kg), whereas weight gain is an important indicator of fetal growth. Maternal weight before pregnancy and weight gain during pregnancy is a major determinant of infant weight at birth. The purpose of this study was to determine the relationship between maternal weight gain during pregnancy with birth weight in the Wonoayu Village Pilangkenceng District Madiun. This research used the analytical method with a "cross-sectional". Independent variable was weight pregnant women and the dependent variable was the weight of newborns. The population in this study were all mothers with babies at birth in the Sumbersono Village Pilangkenceng District Madiun in 2013 as many as to 51 respondents. Samples were 45 respondents drawn used cluster random sampling technique. Source of data used secondary data through the cohort. Analysis of the data relationship between two variables used chi Square.The results showed the majority of pregnant women experience weight gain in normal category as many as 24 people (68.6%) and almost all LBW infants did not experience as many as 29 people (82.9%).The results obtained chi square test of significance value fisher exact test = 0.007 <0.05 so that H1 accepted and H0 was rejected, which means there was a relationship maternal weight gain during pregnancy with birth weight in the Wonoayu Village Pilangkenceng District Madiun. The results showed concordance between field theory with facts where a mothers weight during pregnancy showed a lack of nutritional intake during pregnancy. This has resulted in a lack of fetal nutrition asupuan and hinder the development of the fetus. Health workers should always provide education regarding nutritional needs during pregnancy and also to monitor maternal and fetal development that can be taken immediately if found abnormalities of pregnancy.Keywords: maternal weight gain during pregnancy, birth weight